Fancy Theories of Interpretation Aren't - Larry Alexander (Washington University Law Quarterly, 1995)
The problems with fancy theories are that they are not theories of interpretation, they are not internally consistent, and they are not held sincerely.
Keywords: Linguistics; Law and linguistics